A classication of homothetical hypersurfaces in Euclidean spaces via Allen determinants and its applications - Aydin, Muhittin Evren; Ergut, Mahmut (Balkan Society of Geometers, 2015)
The present authors, in [3], classied the composite functions of the form f = F (h1 (x1) × ... × hn (xn)) via the Allen determinants used to calculate the Allen's elasticity of substitution of production functions in microeconomics. In this paper, we adapt this classication to the homothetical hypersurfaces in the Euclidean spaces. An application for the homothetical hypersurfaces is also given. © Balkan Society of Geometers, Geometry Balkan Press 2015.
Keywords: Allen's matrix; Cobb-Douglas production function; Gauss-Kronocker curvature; Hessian matrix; Homothetical hypersurface; Production function